Clinical, electrophysiological, and molecular findings in early onset hereditary neuropathy with liability to pressure palsy. Issue 6 (30th October 2014) - Potulska‐Chromik, Anna; Sinkiewicz‐Darol, Elena; Ryniewicz, Barbara; Lipowska, Marta; Kabzińska, Dagmara; Kochański, Andrzej; Kostera‐Pruszczyk, Anna
ABSTRACT Introduction: The first episode of hereditary neuropathy with liability to pressure palsy (HNPP) in childhood is rare. Methods: We analyzed retrospectively the data of 7 patients with a deletion in PMP22 and onset of symptoms before age 18 years. Direct sequencing of the LITAF (lipopolysaccharide‐induced tumor necrosis factor) gene was performed in patients and family members. Results: Clinical presentations varied from mononeuropathies to brachial plexopathy, with recurrent episodes in 4 patients. Electrophysiological abnormalities characteristic for HNNP were found in most subjects. Analysis of the LITAF gene revealed an Ile92Val polymorphism in 6 of 7 (86%) probands and 5 of 7 (83%) family members, over 4 times greater frequency than in the general population. Conclusions: Clinical suspicion of HNPP even when nerve conduction study results do not fulfill HNPP criteria should indicate genetic testing. In our patients, early‐onset HNPP was associated frequently with isoleucine92valine LITAF polymorphism. Muscle Nerve 50: 914–918, 2014